Engineering Corynebacterium glutamicum for efficient production of succinic acid from corn stover pretreated by concentrated-alkali under steam-assistant conditions. (June 2023) - Li, Kai; Li, Cheng; Zhao, Xin-Qing; Liu, Chen-Guang; Bai, Feng-Wu
Graphical abstract: Highlights: Constructing a succinate high-producing C. glutamicum . Introducing two xylose utilization pathways into C. glutamicum . Developing CASA pretreatment with high sugar yield and low black liquid. Achieving efficient succinate production from corn stover by engineered C. glutamicum . Abstract: Corynebacterium glutamicum was developed for efficient production of succinic acid from corn stover (CS) pretreated by concentrated-alkali under steam-assistant (CASA) conditions. First, C. glutamicum was engineered by 1) blocking the by-products pathways (deletion of ldh, pta-ackA, and cat ), 2) enhancing the carbon flux to succinate (overexpression of pyc and ppc ), and 3) releasing the end-product inhibition (overexpression of Ncgl0275 ). The recombinant strain produced 117.8 g/L succinate in fed-batch fermentation. Second, to fully utilize xylose in lignocellulosic hydrolysate, two xylose utilization pathways—the isomerase pathway and the Weimberg pathway—were introduced into the recombinant strain. Third, CS was pretreated by CASA with a higher sugars yield and a lower black liquid. Finally, 64.16 g/L of succinic acid was obtained from 150 g/L CASA-pretreated CS by engineered C. glutamicum . These results showed a succinate high-producing C. glutamicum strain using glucose and xylose simultaneously as well as an effective and environmentally acceptable pretreatment strategy.